login
p-INVERT of (1,0,1,0,0,0,0,...), where p(S) = (1 - S)^4.
2

%I #4 Sep 11 2017 12:07:03

%S 4,10,24,55,116,234,460,879,1640,3006,5424,9650,16964,29510,50852,

%T 86893,147360,248198,415440,691428,1144772,1886270,3094292,5055140,

%U 8227084,13341756,21564360,34746331,55823080,89439056,142928424,227851285,362396564,575135150

%N p-INVERT of (1,0,1,0,0,0,0,...), where p(S) = (1 - S)^4.

%C Suppose s = (c(0), c(1), c(2), ...) is a sequence and p(S) is a polynomial. Let S(x) = c(0)*x + c(1)*x^2 + c(2)*x^3 + ... and T(x) = (-p(0) + 1/p(S(x)))/x. The p-INVERT of s is the sequence t(s) of coefficients in the Maclaurin series for T(x). Taking p(S) = 1 - S gives the "INVERT" transform of s, so that p-INVERT is a generalization of the "INVERT" transform (e.g., A033453).

%C See A291728 for a guide to related sequences.

%H Clark Kimberling, <a href="/A291727/b291727.txt">Table of n, a(n) for n = 0..1000</a>

%H <a href="/index/Rec#order_12">Index entries for linear recurrences with constant coefficients</a>, signature (4, -6, 8, -13, 12, -10, 12, -6, 4, -4, 0, -1)

%F G.f.: -(((-1 + x) (1 + x^2) (2 + x + x^2) (2 - 2 x + x^2 - 2 x^3 + 2 x^4 + x^6))/(-1 + x + x^3)^4).

%F a(n) = 4*a(n-1) - 6*a(n-2) + 8*a(n-3) - 13*a(n-4) + 12*a(n-5) - 10*a(n-6) + 12*a(n-7) - 6*a(n-8) +4*a(n-9) - 4*a(n-10) - a(n-12) for n >= 13.

%t z = 60; s = x + x^3; p = (1 - s)^4;

%t Drop[CoefficientList[Series[s, {x, 0, z}], x], 1] (* A154272 *)

%t Drop[CoefficientList[Series[1/p, {x, 0, z}], x], 1] (* A291727 *)

%Y Cf. A154272, A291728.

%K nonn,easy

%O 0,1

%A _Clark Kimberling_, Sep 08 2017